2007
DOI: 10.1016/j.biomaterials.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Engineering adipose-like tissue in vitro and in vivo utilizing human bone marrow and adipose-derived mesenchymal stem cells with silk fibroin 3D scaffolds

Abstract: Biomaterials derived from silk fibrion prepared by aqueous (AB) and organic (HFIP) solvent based processes, along with collagen (COL) and poly-lactic acid (PLA) based scaffolds were studied in vitro and in vivo for their utility in adipose tissue engineering strategies. For in vitro studies, human bone marrow and adipose-derived mesenchymal stem cells (hMSCs and hASCs) were seeded on the various biomaterials and cultured for 21 days in the presence of adipogenic stimulants (AD) or maintained as noninduced cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
274
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 338 publications
(279 citation statements)
references
References 57 publications
4
274
0
Order By: Relevance
“…In their study, hASCs (and hMSCs) cultured on all biomaterials in the presence of AD showed significant upregulation of adipogenic mRNA transcript levels (e.g. GLUT4) to similar extents when compared to noninduced controls (Mauney, et al;. Also, oil-red O analysis of hASC-seeded scaffold displayed substantial amounts of lipid accumulating adipocytes following cultivation with AD.…”
Section: Biomaterials In Tissue Engineering With Ascsmentioning
confidence: 87%
See 3 more Smart Citations
“…In their study, hASCs (and hMSCs) cultured on all biomaterials in the presence of AD showed significant upregulation of adipogenic mRNA transcript levels (e.g. GLUT4) to similar extents when compared to noninduced controls (Mauney, et al;. Also, oil-red O analysis of hASC-seeded scaffold displayed substantial amounts of lipid accumulating adipocytes following cultivation with AD.…”
Section: Biomaterials In Tissue Engineering With Ascsmentioning
confidence: 87%
“…collagen type I) biomaterials (Meinel, et al;. The slow degradation and mechanical integrity of silk scaffolds in comparison with other conventional biomaterials such as collagen and PLA, above all for long-term in vivo studies, suggest that silk fibroin-based scaffolds would be an optimal biomaterial for long-term adipose tissue growth and function (Mauney, et al;. Also, previous studies have demonstrated the ability of adipocytes to secrete various paracrine factors which can positively influence both the migration and differentiation of preadipocytes (Shillabeer, et al;.…”
Section: Biomaterials In Tissue Engineering With Ascsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silk fibroin scaffolds in particular have been previously shown to support adipose tissue formation. 20 Thus, investigating physiological responses to hyperinsulinemia in 3D studies may provide significant insight into mechanisms observed in vivo that may not have been evident in 2D models, as well as serve as a potential tissue model in which adipose-related therapies can be developed and tested.…”
Section: Discussionmentioning
confidence: 99%